Effectiveness of Mulligan Natural Apophyseal Glides as an Adjunct to Conventional Physiotherapy in Recreational Surfers with Non-Specific Low Back Pain: A Randomized Study - Putra, I Putu Yudi Pramana; M. Widnyana; Utama, A.A Eka Septian; Winaya, I Made Niko; Sutyawan, I Wayan Eka (Babali Publisher, 2026)
Background: Non-specific low back pain (NSLBP) commonly affects recreational surfers and leads to functional limitations; however, conventional physiotherapy often focuses on symptom relief, leaving a gap in addressing underlying biomechanical dysfunctions. Evidence on the added value of Mulligan’s Natural Apophyseal Glides (NAGs) in this population remains limited. Methods: This experimental study used a randomized pretest–posttest two-group design conducted at a physiotherapy clinic in Bali (2024). A total of 32 male surfers aged 30–40 years with NSLBP were selected using purposive sampling and allocated into two groups (n=16 each). The independent variables were conventional physiotherapy and conventional physiotherapy combined with Mulligan’s NAGs and ultrasound therapy, while the dependent variable was functional ability measured using the Modified Oswestry Disability Index (MODI). Interventions were administered three times per week for three months. Data were analysed using paired sample t-tests (within-group) and independent t-tests (between-group). Results: Both groups demonstrated improvement; however, the group receiving additional Mulligan’s NAGs showed greater reduction in MODI scores (31.13% ± 3.341) compared to the conventional group (29.09% ± 2.731), with a statistically significant difference (p = 0.002). Conclusion: The addition of Mulligan’s NAGs is more effective in improving functional outcomes in NSLBP. Clinically, nurses and rehabilitation providers should consider integrating biomechanical-based interventions alongside conventional therapy to optimize patient recovery.